(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Age determination in living individuals, dead persons & in human remains may shed light on issues with notable legal and social consequences for individuals as well as for the community. In the age determination of the deceased individual; the post-mortem circumstances can change the body parts and make age estimation difficult. In such cases, skeletal remains are extremely helpful for age determination. This study focuses on investigating the relationship between the stage of fusion of tri-radiate cartilage of innominate bone & biological age in population of Central India. This study was carried out in 120 healthy subjects (60 males and 60 females) aging from 12 to 18 years. The obtained results revealed that the complete fusion of tri-radiate cartilageis seen at 16-17 years. Comparatively, females were developing union at a younger age than their male counterparts. Results also suggest that the age of fusion of tri-radiate cartilage is found to vary greatly all over the India & world, indicating the need for separate standards for separate regions.